ONYCHOMYCOSIS COURSE OF THE DISEASE AND TREATMENT CORRECTION - Oripov R.A. (PEDAGOGS, 2024)
Abstract: this article attempts to reveal the main reasons for the influence of the duration of autoimmune pathology on the effectiveness of the treatment of onychomycosis of the feet. To carry out scientific work, the author observed 150 patients in the rheumatology department of the Altai Regional Clinical Hospital aged 18 to 70 years with autoimmune pathology and onychomycosis of the feet. The control group included 115 patients with onychomycosis of the feet without concomitant somatic diseases, examined and treated in the consultative and diagnostic department. The problem in question is still little studied, therefore, requires more thorough research.